Surface Modified Carvacrol-rich Satureja khuzestanica Essential Oil Nanoemulsion: A Novel Paclitaxel Formulation Induced Apoptosis on Paclitaxel-Resistant Breast Cancer Cells - Zeinab Mazarei; Houri Sepehri; Ladan Delphi; David Julian McClements; Hasan Rafati (Pharmaceutical Sciences, 2024)
Background: The ability of cancer cells to develop multidrug resistance (MDR) is a major challenge in modern chemotherapy. The current generation of commercially available paclitaxel formulations have not been designed to treat resistant tumours. In this study, a nanoemulsion-based delivery system was developed to enhance the efficacy of paclitaxel against resistant breast cancer cells. Methods: The nanoemulsion was formulated using carvacrol-rich Satureja khuzestanica essential oil. Modification of nanoemulsion was performed by incorporating tocopheryl polyethylene glycol 1000 succinate (TPGS) which could inhibit drug resistance in cancer cells. Fabrication of paclitaxel nanoemulsion was performed by high speed homogenization. The cytotoxicity of prepared formulation against resistant breast cancer cells was investigated by MTT assay. Flow cytometry technique was used for cell cycle arrest analysis and examination of the apoptosis induction ability of prepared nanoemulsion. Results: The nanoemulsion had a relatively small mean droplet diameter (93.6 ± 4.2 nm) and good long-term stability. The ability of paclitaxel to inhibit P-gp function in paclitaxel-resistant breast cancer cells (MCF-7/PTX) was synergistically enhanced by administering it within the nanoemulsion. The cytotoxicity of the prepared nanoemulsion on the HUVEC normal cells was much lower than that of MCF-7/PTX cells. Cell cycle analysis utilizing flow cytometry showed that the paclitaxel-loaded nanoemulsion promoted G2-M arrest. Flow cytometry also demonstrated that this nanoemulsion induced apoptosis in MCF-7/PTX cells. Interestingly, apoptosis increased from 20.0% for the free paclitaxel treated group to 85.2 % for the paclitaxel-loaded nanoemulsion treated group. Conclusion: This novel paclitaxel nanoemulsion efficiently suppressed the drug resistance of breast cancer cells and induced effective apoptosis in very low concentrations of paclitaxel.